Clinical outcome of post placental copper T380A and copper 375 IUCD insertion in women delivering by caesarean section - Divya., Divya; Dewan, Rupali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective of the study was to compare the clinical outcome (safety, efficacy, expulsion and continuation rates) of post placental insertion of Cu375 and CuT380A intrauterine contraceptive devices (IUCD) in primiparous women undergoing caesarean section. Methods: This was a prospective, randomized comparative study in which 300 primiparous women were recruited. All these women had post placental intracaesarean insertion of CuT 380A or Cu375 IUCD. Follow up visits were scheduled at 1, 3 months, 6 month and 12 months. Results: Mean age was 23.1 years. Visibility of strings increased in successive follow up visits and was visible in 97.1% of women at the end of one year and 72.3% in CuT380A IUCD users at 12 months. Menorrhagia was reported in 8.6% in Cu375 IUCD users and 10% in CuT380A IUCD users at the end of 1 year of follow up. There were only 10 expulsions of Cu375 IUCD and six that of CuT380A IUCD. Removal rate in was 7.3% in Cu375 users and 6.7% in CuT380A users. Overall 84.7% of the women were satisfied with the treatment and 60% to an extent that they would like to recommend it to others whereas 15.3% were not satisfied at all either due to adverse events or spontaneous expulsion of IUCD. Conclusions: The Gross cumulative continuation rates was 86% in women with Cu375 IUCD insertions and 89.3% in CuT380A IUCD users. There was no significant difference between Cu375 and CuT380A regarding the safety, efficacy and complications.